Anne of avonlea - MONTGOMERY, L.M.; L.M. MONTGOMERY (New York Dell Laurel-Leaf, 1992)
follows 16-year-old Anne Shirley as she begins her career as the new schoolteacher in Avonlea.
Keywords: she transitions from a spirited teenager into a young woman taking on adult responsibilities in the village of Avonlea; personal growth, community responsibility, and finding beauty in daily life